Studi Kualitas Permukaan Pembubutan Kering Pada Baja Aisi 4340 (± 35 HRC) Menggunakan Pahat PVD dan CVD Berlapis - Junaidi; Yulfitra; W Setiawan (Cered Indonesia Institute, 2023)
The machining operation should be targeted at dry or near dry machines to avoid environmental problems associated with the use of cutting fluids. To overcome the above situation, 80% of all machining operations are carried out with superior cutting tools such as CBN and ceramics. However, the price for the lathe chisel is still quite expensive. Cheaper carbide cutting tools are seen as a possible replacement for CBN and Ceramic insert cutting tools and are mostly processed by chemical vapor deposition (CVD) and physical vapor deposition (PVD) techniques. Therefore, a study was conducted on the performance of both PVD tools and CVD coated tools which is very important to recommend the appropriate tool for machining AISI 4340 steel. The workpiece used in this research is AISI 4340 steel (±35 HRC) and the tool used is plated PVD and CVD chisels. The tool used in this study to measure surface roughness is the Stylus Profilometer. The turning process is carried out with 8 cutting conditions using a CNC lathe. In this dry turning research, the most significant variables on surface roughness, surface roughness mathematical equations and also optimal cutting conditions were found, namely cutting speed (v) = 180 m/min, feed motion (f) = 0.2 mm/rev and depth cut (a)= 0.2mm and surface roughness (Ra)= 2.178 micron.